"Subhiksha": The Saga of the Rise and Fall of India’s Sam - R. S., Sathyanarayanan (Indian Journal of Marketing, 2012)
Once a poster boy of India’s booming retail sector, Subhiksha, a chain of discount stores, brought its shutters down in India after a brief expansion spree. The retail chain closed around 1600 stores across the country, which came as a bolt from the blue for Mr. R. Subramanian, a new-generation entrepreneur who started the discount chain "Subhiksha". Fall in realty prices, credit crunch, and slump in demand proved to be a fatal combination for Subhiksha’s downfall though the founder attributed the fact to debt led expansion and subsequent credit squeeze due to the global financial meltdown. This case explores the reasons behind the rise and fall of India’s Sam.